2019
DOI: 10.1016/j.seizure.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Does public attitude change by labeling a person as epileptic, person with epilepsy or the acronym PWE? A systematic review

Abstract: It is still unknown if attitudinal differences by diverse labeling of persons with epilepsy could be universally accepted with the actual literature evidence. The manner in which questions are constructed could also have an impact in final results. The purpose of this systematic review was to examine the published articles regarding changes in public´s attitude towards epilepsy by labeling a person as epileptic, person with epilepsy or with the acronym PWE.Methods: We undertook a systematic review of the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The review of related literature to identify, analyze and construct the questions included in our survey was published in another article [16]. The designed questionnaires collected information on age, gender, practicing religion, socioeconomic status of residence, knowing someone with epilepsy and 14 questions about attitudes towards people with epilepsy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review of related literature to identify, analyze and construct the questions included in our survey was published in another article [16]. The designed questionnaires collected information on age, gender, practicing religion, socioeconomic status of residence, knowing someone with epilepsy and 14 questions about attitudes towards people with epilepsy.…”
Section: Methodsmentioning
confidence: 99%
“…It is also possible that by negative wording or by establishing comparison in the questions the answers could be inducted in the studies of Brazil and Croatia [25,26]. The authors of this study put special attention in avoiding induction by placing neutral personal directed questions [16].…”
Section: Labeling Typementioning
confidence: 97%
“…In two experiments, female silhouettes were judged to be more alike and similar in weight when they were sorted into categories of eating-disorder labels (Foroni & Rothbart, 2011, which is evidence that the diagnostic labels fostered a stereotypical perception of the silhouettes. Carrizosa-Moog et al (2019) and Cutler and Ryckman (2019) reported experimental evidence for negative label effects caused by different clinical labels, such as delusional disorder, schizophrenia, bipolar disorder, major depressive disorder, alcohol use disorder, and epilepsy. In addition, both studies showed that speaking about mentally ill people in a manner that identifies patients with their disorder (e.g., "He is an epileptic" or "She is delusional") can lead to even more negative label effects.…”
Section: Negative Effects Of Mental-disorder Labelsmentioning
confidence: 99%
“…Cuttler and Ryckman (2019) manipulated the presence of the labels delusional disorder, schizophrenia, bipolar disorder, major depressive disorder, and alcohol use disorder and found a negative impact on ratings of perceived aggressiveness, attention-seeking, incompetence, confusion, disorganization, embarrassment, unreliability, unhappiness, and volatility. Finally, there is evidence that labels which identify the person with the disorder (e.g., "He is an epileptic") cause even worse judgements about the person than labels implying that a person has a certain disorder (e.g., "He has epilepsy"; Carrizosa-Moog et al, 2019;Cuttler & Ryckman, 2019).…”
Section: Mental Health Stigmamentioning
confidence: 99%
“…The reasoning outlined above gives rise to concerns about stigmatization of students with learning and behavioral disorders. People in general tend to associate diagnostic labels with stereotypical attitudes (e.g., Carrizosa-Moog et al, 2019;Cuttler & Ryckman, 2019) and teachers might be no exception to the rule. Take the example of ADHD.…”
mentioning
confidence: 99%